Empowering Voices, Bridging Worlds: The Potential of Photovoice for Empowerment, Reflection, and Connection in Diverse Societies - Carmen S. Lienen; Andrea Monica Frisch; Agostino Mazziotta; Anette Rohmann (Social Work and Society)
The present article analyzes the potential of the photovoice method in diverse societies. Photovoice is a community-based participatory action research method with a photojournalistic, socio-critical approach that prioritizes the lived experiences of people belonging to marginalized communities. In photovoice projects, people take photos of their lives to identify community struggles and strengths, which are then collectively discussed and used to facilitate positive social change at the policy level. The article explores to what extent photovoice can benefit diversity within social work by I) supporting the understanding and empowerment of clients through a lifeworld orientation, II) enhancing social workers’ self-reflection on their own identity, role, and mission, and III) strengthening client-provider relationships. Limitations, possible non-intended effects, and potential ethical challenges of the implementation of photovoice in diverse societies are discussed. We conclude the article with practical recommendations on how social workers can incorporate photovoice into their professional practice.